Treatment outcome of twenty-two patients with guanidinoacetate methyltransferase deficiency: An international retrospective cohort study. (May 2018) - Khaikin, Yannay; Sidky, Sarah; Abdenur, Jose; Anastasi, Arnaud; Ballhausen, Diana; Buoni, Sabrina; Chan, Alicia; Cheillan, David; Dorison, Nathalie; Goldenberg, Alice; Goldstein, Jennifer; Hofstede, Floris C.; et al.
Abstract: Purpose: Guanidinoacetate methyltransferase (GAMT) deficiency is an autosomal recessive disorder caused by pathogenic variants in GAMT . Brain creatine depletion and guanidinoacetate accumulation cause developmental delay, seizures and movement disorder. Treatment consists of creatine, ornithine and arginine-restricted diet. We initiated an international treatment registry using Research Electronic Data Capture (REDCap) software to evaluate treatment outcome. Methods: Physicians completed an online REDCap questionnaire. Clinical severity score applied pre-treatment and on treatment. Results: There were 22 patients. All had developmental delay, 18 had seizures and 8 had movement disorder. Based on the clinical severity score, 5 patients had a severe, 14 patients had a moderate and 3 patients had a mild phenotype. All patients had pathogenic variants in GAMT . The phenotype ranged from mild to moderate in patients with the most common c.327G > A variant. The phenotype ranged from mild to severe in patients with truncating variants. All patients were on creatine, 18 patients were on ornithine and 15 patients were on arginine- or protein-restricted diet. Clinical severity score improved in 13 patients on treatment. Developmental delay improved in five patients. One patient achieved normal development. Eleven patients became seizure free. Movement disorder resolved in four patients. Conclusion: In our small patient cohort, there seems to be no phenotype–genotype correlation. Creatine and ornithine and/or arginine- or protein-restricted diet were the most useful treatment to improve phenotype. Highlights: Assessment of treatment outcome in 22 patients using clinical severity score. New treatment algorithm based on the GAMT symptoms. Normal neurodevelopmental outcome in one patient on early treatment.